Predictors of hypertension among rural people of western Maharashtra: a multivariate analysis - Kharde, Anup L.; Phulambrikar, Rutuja M.; Deshpande, Jayant D.; Mahavarkar, Varsha N.; Kharde, Amruta A. (International Journal Of Community Medicine And Public Health, 2019)
Background: Hypertension causes morbidity as well as increases mortality either by acting independently or by affecting multiple organ system. Risk factors of hypertension are categorized as modifiable or non-modifiable risk factors. Early identification of these risk factors is not only essential for prediction of hypertension and but also to reduce effect associated with it. Methods: The present descriptive cross-sectional study was carried out at field practice area of tertiary care teaching hospital of western Maharashtra. Total 1537 sample sized was achieved using systematic random sampling technique. All the village individuals, both male and female, over 18 years of age were included in the study whereas, pregnant women, extremely debilitated persons and subjects who were not willing to give informed consent were excluded. A pre-designed and pre-tested questionnaire was used for data collection. Results: In present study the prevalence of hypertension and pre-hypertension was 11.49% (117). On regression analysis risk factors like age, BMI, high salt intake, family history of blood pressure etc., were found to be associated with hypertension. Conclusions: The present study showed a higher prevalence of both hypertension among the rural population and risk factors such as age, obesity, elite social class, high salt intake, family history of blood pressure were the predictors of the hypertension.